2015
DOI: 10.4103/0019-557x.169649
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and reasons for substance use among long-distance commercial drivers in a Nigerian city

Abstract: The reason for drug use in long-distance drivers could be used to modify the pattern of use to minimize the risk associated with drugged driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…[ 56 ] A similar pattern of use was reported among commercial drivers in Kaduna metropolis. [ 57 ] Alti-Muazu and Aliyu reported the use of marijuana (25.8%) and solution (24.5%), respectively, among commercial motorcyclists in Zaria city, North West Nigeria. [ 58 ] Drug abuse and illicit substance use are also associated with urban violence and crime that are often related to stresses of poverty in our cities.…”
Section: Ain F Eatures Of the mentioning
confidence: 99%
“…[ 56 ] A similar pattern of use was reported among commercial drivers in Kaduna metropolis. [ 57 ] Alti-Muazu and Aliyu reported the use of marijuana (25.8%) and solution (24.5%), respectively, among commercial motorcyclists in Zaria city, North West Nigeria. [ 58 ] Drug abuse and illicit substance use are also associated with urban violence and crime that are often related to stresses of poverty in our cities.…”
Section: Ain F Eatures Of the mentioning
confidence: 99%
“…Peer pressure is a recognized driving force for cigarette smoking and in our study having friends who smoke which may lead to peer pressure also increased the odds of being a current smoker 21 23 . However, we cannot conclude from this cross-sectional study that this association implies causality, although it is likely, but it is reasonable to assume that smoking partly drives social networks and maybe vice versa.…”
Section: Discussionmentioning
confidence: 57%
“…Regarding the use of other psycho-active substances, our finding corroborates previous reports of high rates of psycho-active substance use among long distance drivers. Most drivers refer to fighting fatigue and promoting alertness as the reason for use; however, psycho-active substances have been associated with increased risk of road traffic accidents (RTAs) 4 , 14 , 21 , 27 – 28 . Although a study in Australia has reported reduced RTAs in users of caffeinated products, it is important to note that the Australian drivers are usually regulated and have a maximum number of driving hours stipulated by law which is not the case for most long distance drivers in Nigeria 29 .…”
Section: Discussionmentioning
confidence: 99%